Reciprocal regulation by TLR4 and TGF-β in tumor-initiating stem-like cells - Chen, Chia-Lin (American Society for Clinical Investigation, 2013)
Tumor-initiating stem-like cells (TICs) are resistant to chemotherapy and associated with hepatocellular carcinoma (HCC) caused by HCV and/or alcohol-related chronic liver injury. Using HCV Tg mouse models and patients with HCC, we isolated CD133(+) TICs and identified the pluripotency marker NANOG as a direct target of TLR4, which drives the tumor-initiating activity of TICs. These TLR4/NANOG–dependent TICs were defective in the TGF-β tumor suppressor pathway. Functional oncogene screening of a TIC cDNA library identified Yap1 and Igf2bp3 as NANOG-dependent genes that inactivate TGF-β signaling. Mechanistically, we determined that YAP1 mediates cytoplasmic retention of phosphorylated SMAD3 and suppresses SMAD3 phosphorylation/activation by the IGF2BP3/AKT/mTOR pathway. Silencing of both YAP1 and IGF2BP3 restored TGF-β signaling, inhibited pluripotency genes and tumorigenesis, and abrogated chemoresistance of TICs. Mice with defective TGF-β signaling (Spnb2(+/–) mice) exhibited enhanced liver TLR4 expression and developed HCC in a TLR4-dependent manner. Taken together, these results suggest that the activated TLR4/NANOG oncogenic pathway is linked to suppression of cytostatic TGF-β signaling and could potentially serve as a therapeutic target for HCV-related HCC.